The hypothesis of contact in nursing: a narrative review of the literature - Marletta, Giuseppe; Artioli, Giovanna; Sarli, Leopoldo; Mancini, Tiziana (Acta Biomedica Atenei Parmensis, 2015)
Background and aim: In Social Psychology, in relation to the effects of contact, there are two theoretical strands apparently fighting against each other: to one side, the contact hypothesis of Allport according to which, the meeting between members of different groups can, if managed in favorable conditions, reduce prejudice, on the other side, the Social Identity Theory of Tajfel and Turner, according to which the comparison between people belonging to different groups may actually generate an attitude of ingroup favoritism and outgroup discrimination. The aim of this review was to analyze how the literature has dealt with the problem of contact with people from different cultures in relation to its outcomes taking into account the environment of nursing. Method. Systematic review. Results. There is sufficient evidence that contacts by race / ethnicity, present in nursing-education settings, in the relationship among nurse practitioners, and between nurses and patients, they produce discriminations and prejudices. The contact in the workplace shows however, also favorable outcomes, highlighting then contradictory results. Conclusions. The scarcity of material available in the literature and the inconsistency of results, both as regards to the effects of the contact in the training nursing, and as regards to the effects of the contact in relation to the quality of care provided, does not allow definitive conclusions to support the usefulness of the contact in nursing in terms of reducing prejudices and discriminations. It would therefore be advisable to investigate more deeply the effects of contact in the nursing environment.